John Rawls’ Justice As Fairness: A Political Conception - Yeşilkaya, Nazan (Cankiri Karatekin University, 2022)
The impact of John Rawls’ “justice as fairness” in contemporary society is far and wide since it provides an ethos and condition of fairness as the essential factor in the dispense of justice in the public domain. In this regard, it could be inferred that Rawls’ concept of justice accounts for political liberalism in such a way that central to justice are respect, equality, rationality, reasonableness, freedom, and autonomy of the person that is carried over in the public domain. What made Rawls different is the idea that “justice” and “rationality” can motivate people to undertake social cooperation. As society provides the setting for individuation and the pursuit of good, it motivates people to pursue social collaboration because it is good. Considering the fact that pluralism and diversity of worldviews frame the social life of the individual, Rawls uses the approach of political liberalism to decipher the connection between the individual and the state. Rawls’ political liberalism assumes that shared ideals of justice between different reasonable comprehensive views are possible, and this underlies the basic structure of society and social cooperation. An important aspect of “justice as fairness” is that it does not claim to provide a complete moral or metaphysical doctrine or interpretation of what justice is all about. Instead, “justice as fairness” emphasizes the act of making decisions and choices. Rawls' "justice as fairness" has brought transcendent justice into the domain of human decisions and choices. This article will make a critical assessment of political liberalism to justify “justice as fairness as a political concept”.

John Rawls'un “hakkaniyet olarak adaletin” çağdaş toplumdaki etkisi, kamusal alanda adaletin dağıtılmasında temel faktör olarak bir ahlak ve adalet koşulu sağladığı için oldukça geniştir. Bu bağlamda, Rawls'un adalet kavramının siyasi liberalizmi, adaletin merkezinde saygı, eşitlik, rasyonellik, makullük, özgürlük ve kamusal alandaki kişinin özerkliği olacak şekilde açıkladığı sonucuna varılabilir. Rawls'u farklı kılan, “adalet” ve “rasyonelliğin” insanları sosyal iş birliği yapmaya motive edebileceği fikridir. Toplum, insanlara bireyleşme ve iyiliğin peşinde koşma ortamını sağladığı ve fayda sunduğu için sosyal iş birliğini sürdürmeye motive eder. Çoğulculuğun ve dünya görüşlerinin çeşitliliğinin bireyin toplumsal yaşamını çerçevelediği gerçeğinden hareketle Rawls, birey ve devlet arasındaki bağlantıyı deşifre etmek için politik liberalizm yaklaşımını kullanır. Rawls'un politik liberalizmi, farklı makul kapsamlı görüşler arasında paylaşılan adalet ideallerinin mümkün olduğunu varsayar ve bu, toplumun temel yapısının ve sosyal iş birliğinin temelini oluşturur. “Hakkaniyet olarak adalet”in önemli bir yönü, adaletin neyle ilgili olduğuna dair tam bir ahlaki veya metafizik doktrin veya yorum sağlama iddiasında olmamasıdır. Bunun yerine, “hakkaniyet olarak adalet”, karar verme ve seçim yapma eylemini vurgular. Rawls'un "hakkaniyet olarak adalet"i, aşkın adaleti insan kararlarının ve seçimlerinin alanına getirir. Bu makale, “siyasi bir kavram olarak hakkaniyet olarak adalet”i haklı çıkarmak için siyasi liberalizmin eleştirel bir değerlendirmesini yapmaktadır.
Politik Bir Anlayış Olarak John Rawls’da Hakkaniyet Olarak Adalet
Keywords: Religious Studies; Din Araştırmaları